13 art techniques children should know - Wenzel, Angela; Hall, Cynthia (Munich : Prestel, 2013)
Introduces children to thirteen important artistic techniques via specific works of art. Includes timeline, glossary, and quiz questions.--
Translated from the German.
Originally published as: 13 Techniken, die du kennen solltest.
Keywords: Art -- Technique -- Juvenile literature; Artists' materials -- Juvenile literature; Artists -- Juvenile literature; Art -- Technique; Artists' materials; Artists; Art appreciation; Art -- Technique; Artists; Artists' materials; Juvenile works